2020
DOI: 10.3390/electronics9040611
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Guidelines of Head-Up Display User Interface during Semi-Automated Driving

Abstract: Self-driving vehicles are emerging as a result of technological advances, and the range of human behavior is expanding. The collateral information on driving is increasing, and head-up displays (HUDs) can be coupled with augmented reality displays to convey additional information to drivers in innovative ways. Interference between the actual driving environment and the displayed information can cause distractions. Research is required to find out what information should be displayed and how to properly display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The autonomous vehicle we seek to develop will actively interact with its driver based on the multimodal interface [ 24 ], and haptic research and development will need to be conducted accordingly. Particularly in terms of semi-autonomous driving, the effect of a visual display, such as a HUD, would be appropriate, as drivers look straight ahead [ 25 ]. However, in autonomous driving, signals must be presented according to a driver’s state (sleep, watching a movie, reading, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The autonomous vehicle we seek to develop will actively interact with its driver based on the multimodal interface [ 24 ], and haptic research and development will need to be conducted accordingly. Particularly in terms of semi-autonomous driving, the effect of a visual display, such as a HUD, would be appropriate, as drivers look straight ahead [ 25 ]. However, in autonomous driving, signals must be presented according to a driver’s state (sleep, watching a movie, reading, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Design proposals incorporate a balance between the risks and the advantages of windshield HUDs such as considering driver's abilities and the priority of tasks in every single context of the transportation. [ 58 ] A need for a human‐centered approach in the design of windshield HUDs is paramount for safety and security on roads. [ 59 ] The driver's cognitive and sensory abilities need to be balanced with the driver's needs for windshield HUDs.…”
Section: Introduction To Head‐up Displays (Huds)mentioning
confidence: 99%
“…[ 71 ] Finally, ergonomic studies suggested that the placement and the amount of HUD projection content is crucial. [ 58 ] Fewer than 6 symbols should be displayed at one time and the main content should be placed in the center of the windshield. Gap analysis frameworks can allow for defining metrics for the component arrangement and replay field efficiency to meet the industry requirements for holographic HUDs.…”
Section: Introduction To Head‐up Displays (Huds)mentioning
confidence: 99%
“…Several additional design choices were made in accordance with well-established ergonomic and safety guidelines for in-vehicle electronic devices to limit both the driver's visual-and mental workload, and the glances away from the centre of the road while effectively conveying the necessary information (summarized by: National Highway Traffic Safety Administration, 2013b; Park & Im, 2020). First, all illustrations were placed as close to the centre of the road without blocking the driving situation.…”
Section: Experimental Condition: Digital In-car Tutor (Dit Group)mentioning
confidence: 99%
“…It should be investigated how a specific DIT design affects drivers' gaze patterns, cognitive load and response time and quality. While general recommendations for head-up display visuals have been studied (National Highway Traffic Safety Administration, 2013b;Park & Im, 2020), the specific placement and form of DIT visuals need to be empirically determined so they require minimal cognitive demand and gazes away from the road. In conclusion, although the current DIT prototype is designed to minimize cognitive load and distraction, an important next step would be to investigate the effects of a DITs specific design elements on drivers' attention and ability to respond to emergencies as it is active.…”
Section: Future Research and Development Of An Adaptive Digital In-car Tutormentioning
confidence: 99%